2010
DOI: 10.1063/1.3483300
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire charging in collisionless plasma

Abstract: We calculate the collision cross section of a charged finite cylinder (nanowire) with a beam of ions and electrons in collisionless plasma. We find that, while the shape and area of the cross section has complex dependence on the charge and orientation of the nanowire relative to the charged beam, its orientational average has a remarkably simple form: for attractive interactions, it is a linear function of the electrostatic ratio qjqpe2/4πϵ0L0kT, where qje is the charge of the ions/electrons, qpe is the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The manner in which these results apply to the overall theoretical framework of nonspherical particle charging in general depends on the compactness of the particle geometries 17 , 38 and the flow regime of the charging species 40 . Our results are of fundamental importance in complex plasmas 3 11 , 38 , 40 , aerosol science, 21 26 and astrophysics 14 19 , as well as in numerous applications.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The manner in which these results apply to the overall theoretical framework of nonspherical particle charging in general depends on the compactness of the particle geometries 17 , 38 and the flow regime of the charging species 40 . Our results are of fundamental importance in complex plasmas 3 11 , 38 , 40 , aerosol science, 21 26 and astrophysics 14 19 , as well as in numerous applications.…”
Section: Discussionmentioning
confidence: 75%
“…The charge of clustered particles seems heavily dependent on their morphology, which in turn impacts the particles’ accretion process 17 . In aerosol science, extensive experimental and computational research is reported on the charging of nonspherical particles at atmospheric pressures 21 26 , since particle charge is of vital importance in determining particle size in differential mobility analyzers.…”
Section: Introductionmentioning
confidence: 99%
“…more detailed short range potential interactions than the models employed here), charge exchange upon collision, and exchange of momentum and energy upon collision. Also not examined were aspherical particles and aggregates [23,[51][52][53]; this will require consideration of alignment and rotation in flow, as well as an appropriate drag coefficient [54]. Finally, many instances the dilute approximation is not valid, and multi-body particle interactions (particularly electrostatic) will need to be considered in future collision modeling efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In aerosols and dusty plasmas, oppositely charged particles rapidly aggregate (collide and bind) with one another, while the charging of particles to sufficiently high levels of the same polarity stabilizes them against aggregation [16][17][18][19][20]. Given the importance of charged particle collisions in particleladen flows, numerous efforts have been devoted to developing accurate collision rate models for charged particles [21][22][23]. Many of these efforts consider the combined influences of electrostatic potential interactions and thermal energy on particle motion, such that the number of collisions per unit volume per unit time (R ij ) between particles of type i (size, charge level) and type j can be calculated as: (1) where n i and n j are the number concentrations of particles of type i and type j, respectively, and k ij is the collision rate coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…This shift can be explained by the charging effect of the plasma. [31][32][33][34] Charging by the plasma takes place in only seconds, where chemical/electrochemical charging can take several minutes 24 to hours. 27 This method allows real-time monitoring of the charging effect induced by low-pressure plasmas and could be utilized for photonics applications based on the LSPR shift.…”
mentioning
confidence: 99%